Exploring the acceptability of an internet-based self-management intervention for people with tinnitus: A qualitative study - Kate Greenwell; Neil Coulson (Frontiers Media S.A., 2015)
Background: Tinnitus is a common medical symptom that can affect an individual's emotional and functional quality of life. Psychological therapies are acknowledged as beneficial to people with tinnitus, however, they are not always readily accessible. With their global reach, internet-based interventions have the potential to reduce the disparity in access to psychological support which people with tinnitus currently experience. Aim: This research will explore users' reactions to and interactions with the Tinnitus E-Programme, an internet-based intervention for the self-management of tinnitus that is currently available online. Methods: Ten people with tinnitus have completed the programme and taken part in a semi-structured interview to date. Participants also completed a relaxation log to explore how well they were able to implement the skills they learnt during the programme in their everyday lives. The interview data will be presented. Results: Thematic analysis revealed that, overall, the programme was highly acceptable to its target population. Users valued the provided education about tinnitus and its management, relaxation skills training and cognitive restructuring training. Usage of the tools to self-monitor levels of tinnitus distress was variable and few people reported joining or participating in the online support group. Participants appreciated being able to work flexibly with the programme and engaging with the materials 'offline'. Usability issues meant that some essential programme components were often missed. Conclusions: Findings suggest that the programme offers an acceptable form of tinnitus management for its target group. However, this work also highlighted some key opportunities to improve the programme. In future work, these qualitative findings will be triangulated with the relaxation log data and the findings from a parallel online survey with past users who have used the programme in the real-world. Consistent with a person-based approach, this research will inform the development of a set of guiding principles for future optimisation work.